Transcriptomic and metabolomic analysis clarify the molecular mechanisms underlying the formation of sexual and apomictic Persian walnut (Juglans regia L.) embryos - Bao, Chunjie; Chen, Hong; Zhou, Haoliang; Chen, Feng (Frontiers in Plant Science, 2025)
PurposePersian walnut (Juglans regia L.) is one of the world’s economically significant dry fruits, which stems from the high nutritional value of its kernel and its uses in diverse industries. Walnuts species can employ sexual and apomictic reproductive strategies. Multi-omics analyses of apomictic walnut embryos have not yet been conducted. This study integrates transcriptomic and metabolomic analyses to reveal new insights into the formation of sexual and apomictic walnut embryos, providing a valuable foundation for future research on apomictic embryo development in walnuts.MethodTo elucidate the mechanisms underlying these reproductive modes, transcriptomic and metabolomic analyses were performed on the embryos of sexual and apomictic walnut species at different developmental stages.ResultsOur findings revealed 321 differentially expressed genes (DEGs) and 19 differentially accumulated metabolites (DAMs) in apomictic vs. sexual walnut embryos. The joint transcriptomic and metabolomic analysis revealed that DEGs and DAMs were mainly enriched in metabolic pathways, biosynthesis of secondary metabolites, plant hormone signal transduction, and tryptophan metabolic pathways. The content of DAMs, such as tryptamine, jasmonic acid (JA), and JA-isoleucine, was significantly higher in embryos derived from flowers that had been forced to reproduce apomictically (subjected to polyvinyl alcohol-capped stigma treatment) than embryos derived from flowers that had been subjected to normal artificial pollination. COMT, PME, TAT, CHIB, FG3, CYP82C4, CYP82G1, aceB, SDR, ribBA, AFS1, BHMT2, GN1_2_3, SGR, BAK1, trpB, AOC3, ASN, IAA, TDC, ZEP, JAZ, and ACO were positively correlated with DAMs. 9 genes related to DAMs were verified by real-time quantitative PCR, and their relative expression differences were consistent with the results of the transcriptome analysis. BAK1, trpB, AOC3, ASN, IAA, TDC, ZEP, JAZ, ALDH, and ACO played a role in regulating the formation of apomictic embryos in walnut by regulating DAMs, such as auxin(tryptamine) and JA.ConclusionTRA, JA, and JA-ILE play important roles with metabolites involved in apomixis. BAK1, trpB, AOC3, ASN, IAA, TDC, ZEP, JAZ, ALDH, and ACO may be the key genes involved in apomixis. These candidate genes could be strongly associated with the molecular mechanisms underlying apomixis in walnut were identified, and this will help clarify the formation of apomictic embryos in walnut.